Spray forming of wear and corrosion resistant bimetallic pipes : from the alloy design to the semi- industrial process - Zepon, Guilherme (Universidade Federal de São Carlos, 2016)
The oil exploitation and production at the pre-salt fields in a safety and efficient way depends on the development of materials that withstand the severe work conditions found in these fields. For instance, pipes, such as drilling risers and casings, are often subjected to severe wear and corrosion conditions. This thesis is dedicated to evaluate the technical feasibility to produce wear and corrosion resistant bimetallic pipes by spray forming. The processing-microstructure-properties relationship of the spray-formed boron-modified supermartensitic stainless steel (SMSS) grades was comprehensively studied. Deposits of SMSS with boron contents ranging from 0.3 %wt. to 1.0 %wt. were processed by spray forming. The spray-formed boron-modified SMSS deposits had the wear resistance evaluated through different wear tests and their corrosion resistances by means of electrochemical techniques. It was demonstrated that the wear resistance of the spray-formed boron-modified SMSS is determined by the presence of the eutectic network of M 2B-type borides resulted from the spray forming process. On the other hand, the corrosion resistance of the spray-formed boron-modified SMSS is controlled by the chemical composition of the martensitic matrix. Furthermore, spray-formed bimetallic pipes composed of boron-modified SMSS and conventional SMSS were produced in the unique semi-industrial scale spray-forming plant of the Foundation Institute of Materials Science (IWT-University of Bremen, Germany). The relationship between the process parameters and the metallurgical quality of the pipes was addressed. It was shown that the key to produce a spray-formed bimetallic pipe with good metallurgical quality is adjusting the process parameters in such a way that the deposition zone’s temperature is kept within the alloy’s solidification temperature range during the whole deposition process. Moreover, solidification and grain size evolution models in spray forming were proposed. Finally, the mechanical properties of one of the spray-formed bimetallic pipes in the as-spray formed condition and after heat treatments were evaluated.
Conformação por spray de tubos bimetálicos resistentes ao desgaste e à corrosão : da concepção das ligas ao processamento semi-industrial
Keywords: Ligas; Conformação por spray; Desgaste; Corrosão; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA